2016
DOI: 10.1021/acschembio.5b00996
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Lys and Arg Methylation

Abstract: A network of reader proteins and enzymes precisely controls gene transcription through the dynamic addition, removal, and recognition of post-translational modifications (PTMs) of histone tails. Histone PTMs work in concert with this network to regulate gene transcription through the histone code, and the dysregulation of PTM maintenance is linked to a large number of diseases, including many types of cancer. A wealth of research aims to elucidate the functions of this code, but our understanding of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 96 publications
0
70
0
Order By: Relevance
“…112 Perhaps the ultimate challenge in protein recognition -the recognition of individual residues on an open surface -is difficult, but pioneering work has shown that rare residues such as those post-translationally modified in histone proteins can be successfully targeted. 113 What about enzyme mimicry? The important difference between synthetic hosts and biological ones is one of size, and this leads to other important differences including: polarity, flexibility, and intricacy of the binding motif.…”
Section: Recognition Mimicry and Interactions With Biomoleculesmentioning
confidence: 99%
“…112 Perhaps the ultimate challenge in protein recognition -the recognition of individual residues on an open surface -is difficult, but pioneering work has shown that rare residues such as those post-translationally modified in histone proteins can be successfully targeted. 113 What about enzyme mimicry? The important difference between synthetic hosts and biological ones is one of size, and this leads to other important differences including: polarity, flexibility, and intricacy of the binding motif.…”
Section: Recognition Mimicry and Interactions With Biomoleculesmentioning
confidence: 99%
“…As a consequence, epigenetic regulators have become major targets for drug development 9 . Lysine and arginine methylation play central roles in this “histone code” theory, and these two residues can accept more than one methyl group, with different protein methyltransferases able to execute varying degrees of methylation 10 . Methyl reader domains are clustered into eight major families, including plant homeodomains (PHDs), WD-40 domains, chromatin organization modifier domains (chromodomains), Tudor domains, Agenet domains, proline-tryptophan-tryptophan-proline (PWWP) domains, Bromo adjacent homology (BAH) domains, and malignant brain tumor (MBT) domains 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Histone methylation is completed by S-adenosylmethionine-dependent methyltransferase and occurs on lysine or arginine residues in histone tails (Beaver and Waters, 2016). Histone methylation has been shown to play a role in both transcriptional activation and repression (Wang et al, 2001; Jeong et al, 2011; Kallestad et al, 2014; Figure 2B).…”
Section: Mechanismsmentioning
confidence: 99%